Stand-Alone Tibial Interference Screw Fixation and Tibial Interference Screw Plus Tibial Staple Fixation Produce Comparable Outcomes After Primary Anterior Cruciate Ligament Reconstruction Using Hamstring Autografts - Raed Y. Abudaqqa, M.D; Ahmad R. Abed, M.D; Ahmad A. Toubasi; Ashraf T. Hantouly, M.D., M.Sc; Ali J. Al Mas, M.D; Faris A. Abushaaban, M.D; Kariyal P. Arun, F.R.C.S; Amgad M. Elshoeibi (Elsevier, 2023)
Purpose: To investigate the impact of adding a metal staple alongside the interference screw in tibial side graft fixation during anterior cruciate ligament reconstruction (ACLR). Methods: All patients treated with autograft hamstring ACLR at our institution between January 2017 and December 2021 with a minimum 1-year follow-up were reviewed retrospectively. Patients treated with a stand-alone interference screw for tibial side fixation were compared with those treated with a combination of interference screw and staple. The primary outcome was failure of the reconstructed graft. Secondary outcomes were operative time, complication rate, and reoperation rate. Results: A total of 497 patients met the study's inclusion and exclusion criteria. A combination of staple and interference screw was used in 167 patients (33.6%), whereas a standalone interference screw was used in 330 patients. There was no significant difference between the 2 groups in terms of operative time, complication rate, or failure rate. The mean follow-up was 23.25 (±13.29) months. Conclusions: Our results demonstrate that augmenting the interference screw with a staple for tibial-side fixation in ACLR does not have a significant impact on operative time, reoperation rate, complications, or failure rates. Level of Evidence: Level III, retrospective cohort study.